The making of the “Stadtautobahn” in Berlin after World War Two: a socio-histoire of power about urban automobile infrastructure - Christoph Bernhardt (The Journal of Transport History, 2020)
The paper analyses the West-Berlin pathway to the "car-friendly city" in the context of the Cold War. It starts by retracing some long term continuities since the 1920s and gives special attention to the institutional settings and power struggles within the municipal authorities. The prospective character of the planning for the "Stadtautobahn" since 1945 which was far ahead of the real motorisation of the time is explained by the strong political and ideological intention to demonstrate the superiority of the Western life style. The Berlin case is reflected in the context of projects for ring-roads in other European cities.
Keywords: 710; Berlin automobile infrastructure; ring-roads; transport planning